Real‐time messaging is associated with shorter emergency department length of stay during the COVID‐19 pandemic - Kai‐Wei Lin; Wan‐Ching Lien (Hong Kong Journal of Emergency Medicine)
Abstract Background Effective communication among healthcare workers wearing personal protective equipment (PPE) during the COVID‐19 pandemic posed significant challenges. Objective This study aims to evaluate the relationship between the use of a real‐time communication platform and emergency department (ED) length of stay (LOS) for patients presenting with respiratory symptoms during the pandemic. Methods A real‐time communication platform was developed and integrated into the hospital information system prior to the pandemic. This retrospective study analyzed de‐identified data of ED patients with respiratory symptoms, categorized as triage levels 2–5, from January 2020 to December 2022. Results A total of 47,296 patients were included in the analysis, with 9133 (19%) managed using the communication tool. Nurses exclusively used the tool to remind physicians about patient disposition. Patients managed with the tool experienced significantly shorter LOS, and this effect remained consistent across all triage levels (p < 0.05). Conclusions The use of the real‐time communication tool by ED healthcare workers was associated with a reduction in ED LOS for patients presenting with respiratory symptoms.